Industrial quality control study on Marsman-Drysdale Foods Corporation - Nadal, Gemmalyn P.; Reytiran, Philip; Ong, Michael U. (Diliman, Quezon City College of Engineering, 2003)
An industrial quality control study is conducted on Marsman- Drysdale Foods Incorporated, the food processing company of the Marsman- Drysdale Group that specializes in the processing of fruit juices and purees under the Drysdale brand from the month of June to August, 2002. The Drysdale Mango Nectar which has an 11.4% share in the production volume, is currently the major product of the company, thus focus of this study. With the aid of statistical tools like the Pareto chart, three major problems were identified and concentrated on. These three problems areas are: high number of spillages and bottle breakages in the filling process and spoilage of the product after the incubation period. Through the use of a Cause and Effect Diagram, the root causes of these trouble areas were known to be machine vibration, high filling temperature and improper capping respectively. To better understand these problems, the filling and the capping processes were studied through statistical process control ans process capability analysis. From the constructed control charts, previous data confirmed that the filling process as regards to the spillages was in control through the process average was high. This also means that quality can no longer be improved by any action at the work force level and cannot be resolved without altering the existing system. The capping process however is out of control and non-random as well as the filling process with regard to the filling temperature. Adjustments were then made in order to create in-control charts from which the process capability ratios were calculated. The process capability ratios showed that the capping process is only capable of manufacturing within the specification limits. Production is not capable in terms of filling temperature. In order to address these problems, recommendations were generated for improvement. The proponent recommends that administration would constantly monitor its processes through the conduct of statistical process control over the production system, employ its process engineers to examine deeper the conditions of its machines, and that they follow a regular machine maintenance plan in order to ensure that machines are always working at full capacity. Buying of new machines that are capable of performing the different processes discussed is also as an option if the company wishes to have better operations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Marsman-Drysdale Foods Corporation; Food industry; Quality Control